The Competence of the European Union in Copyright Lawmaking A Normative Perspective of EU Powers for Copyright Harmonization - Ramalho, Ana.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book inquires into the competence of the EU to legislate in the field of copyright, and uses content analysis techniques to demonstrate the existence of a normative gap in copyright lawmaking. To address that gap, it proposes the creation of benchmarks of legislative activity, reasoning that EU secondary legislation, such as directives and regulations, should be based on higher sources of law. It investigates two such possible sources: the activity of the EU Court of Justice in the pre-legislative era and the EU treaties. From these sources, the author establishes concrete benchmarks of legislative activity, which she then tests by applying them to current EU copyright legislation. This provides examples of good and bad practices in copyright lawmaking and also shows how the benchmarks could be implemented in copyright legislation. Finally, the author offers some recommendations in this regard.
1. Introduction -- 2. A Normative Gap in Copyright Lawmaking? -- 3. Colonizing the Normative Gap: The Intervention of the Court of Justice -- 4. Minding the Normative Gap: The EU Treaties -- 5. Bridging the Normative Gap: Proposed Benchmarks for Copyright Lawmaking -- 6. Field-Testing the Normative Bridge: The EU Copyright Acquis -- 7. The Normative Gap: Water Under the Bridge.
Keywords: Law; European Union; International law; Intellectual property -- Law and legislation; European Economic Community literature; Law; International IT and Media Law, Intellectual Property Law; European Law; European Integration; European Union Politics; Electronic books